Urban climate forecasts: From risk to resilience. Milan Innovation District's key design aspects for buildings and infrastructures - Boschi, Nadia (Frontiers in Climate, 2023)
Climate-related transitional and physical risks are relevant to the building industry. This paper focuses on the physical risk as mitigated and embedded into the design of buildings and infrastructures at the Milan Innovation District (MIND). MIND is an Italian development piloting the transition to resilient green urban planning. This paper discusses the methodology adopted at the early stages of urban and building design to assess the local climate change risks and impacts to be mitigated. As per the Intergovernmental Panel on Climate Change (IPCC) and the climate change scenarios are based on projected temperature changes under representative concentration pathways (RCPs). The scenarios considered are 4.5 and 8.5. Climate projections are from the World Bank Change Knowledge Portal and the projected epw Weatherfiles for Milano Linate. These were generated using IES and Weathershift™ tool. The analysis focused on the temperature raise including the masterplan sunlight analysis, the spatial thermal comfort analysis, and the climate change visualization. Results show that the risk of overheating increases. These were discussed in climate change adaptation and resilience planning workshops with a broad range of stakeholders to identify key strategies and functional distribution de-risking strategies. Climate change poses a significant risk to society and resiliency and decarbonization priorities may differ by region. Although, This paper proposes a replicable high-level assessment that can help developers and business leaders in mapping and mitigate the climate capital-related downside risks that have a material impact on their business overall risk profile and capital adequacy.